PENGARUH KEPUASAN TERHADAP LOYALITAS DENGAN MEDIASI KOMITMEN PADA NASABAH BANK BCA KCP NGORO MOJOKERTO - Ika Riskiyati (Journal of Business & Banking, 2012)
Loyalty is the condition in which the customers have positive attitude towards a product both manufactured and service. In addition, the more qualified the product the loyal the customers are. Therefore, it is important for the company to maintain the customers loyalty. This study attempts to provide good input for the banking industries about the product quality and the influence towards the customer loyalty. it was found that how customer satisfaction, loyalty and commitment are defined and related to one another. The data were collected using questionnaire was that this sampling provides judgment such as when implementing this technique the sampling process required such as minimum age of respondents l7 years and more than 45 years, has been long enough to be a customer of minimally 3 months and more than 5 years, and the respondents of this research were the customers of BCA KCP (offce branch) in Ngoro, It was based on 110 responses collected from Bank of BCA KCP Ngoro Mojokerto. The method analysis in this research was Maximum Likelihood test using the program AMOS version 18.0. The results showed that only three hypotheses were accepted; the customer satisfaction towards the customer commitment has a significant influence, customer commitment towards the customer loyalty has a significant influence, and the customer satisfaction towards the customer loyalty with a customer commitment as a mediating has a significant influence.